Antibiotic resistance in Enterotoxigenic and non-enterotoxigenic Escherichia coli. - DeBoy, J M (1980)
Antibiotic disk susceptibility tests were done on 220 strains of Escherichia coli belonging to serotypes reported in the literature to be associated with the production of enterotoxin. A total of 128 (58%) were resistant to one or more antibiotics, sulfa drugs, or chemotherapeutic agents. An analysis of these strains revealed primary, secondary, and tertiary drug resistance patterns that indicated a selective pattern in the formation of multiple drug resistance in E. coli. Resistances to certain antibiotics were more likely to occur in pairs and triads (secondary resistance patterns) that were often combined or coexisted in a single strain of E. coli to produce tertiary drug resistance patterns, conferring drug resistance to five or six different antibiotics. Among enterotoxin-associated serotypes, single and multiple drug resistance was less frequently associated with enterotoxin-produced strains than with strains from the same serotype that were not enterotoxigenic. Within the enterotoxigenic E. coli, single and multiple resistance to antibiotics was more frequent in strains producing only heat-stable enterotoxin (ST) than in strains producing only heat-labile enterotoxin (LT) or both. The number of resistances to different antibiotics per resistant strain averaged approximately 1.4 for LT plus ST or LT strains, and 3.9 for ST strains and nonenterotoxigenic strains. Phenotypic characterization of 170 strains for four usually plasmid-mediated characteristics showed that the number of antibiotics to which a strain was directly resistant varied with the type and number of plasmid-mediated characteristics present.